Technical experts' perspectives of justice-related norms: Lessons from everyday environmental practices in Indonesia. (March 2021) - Lai, Jia Yen; Staddon, Sam; Hamilton, Alistair
Highlights: Intermediaries prioritize distributive & procedural justice over recognition concerns. Patriarchal norms underpin the intermediaries' prioritization of justice. Hierarchical bureaucracy restricts an upward mobilization of justice norms. Social relationships affect the intermediaries' willingness to communicate for justice. Workload, incentives, and safety encourage active engagement of intermediaries. Abstract: The involvement of technical experts in environmental management and their perspectives on environmental justice issues can influence how justice notions become integrated into sub-national policies and programs. In other words, the justice-related norms perceived by technical experts have a huge impact on the delivery of justice for society and local environmental practices. Environmental Impact Assessment (EIA) as the world's most widespread environmental policy tool, provides an opportunity for exploring the incorporation of justice in everyday environmental practices. Specifically, how justice concerns related to global sustainability goals might be promoted or shutdown at the sub-national level through the actions of the technical experts involved i.e., those referred to here as 'intermediary actors.' This article reports on research which used semi-structured interviews to investigate the justice-related norms prioritized and promoted by intermediary actors, namely consultants, academics, and governmental officers, in the technical review process of EIA in Indonesia. It also examined the facilitating or constraining factors for negotiating and mobilizing those norms in the project debates of EIA at the sub-national level. We find that the intermediaries engaged with prioritized issues of justice unevenly, as they prioritized distributive and procedural justice over recognitional concerns. Our findings also uncovered crucial structural factors that have preserved existing unequal power relationships in a decentralized environmental governance system. Traditional and authoritative customs underlying environmental policies and practices therefore have significantly influenced the prioritization of justice-related norms. These social and cultural contexts have also restricted an upward mobilization of justice concerns from the sub-national to national and international governance levels. This study argues that the intermediaries need various institutional, physical, and social resources to advance global sustainability and justice agendas at the sub-national level via existing national environmental management tools.